How does a failed quit attempt among regular smokers affect their cigarette consumption? Findings from the International Tobacco Control Four-Country Survey (ITC-4) - Yong, Hua-Hie (Nicotine Tob Res, 2008)
Recent cross-sectional data suggests that smokers tend to reduce smoking following a failed self-initiated quit attempt, possibly motivated by the need to reduce harms or to facilitate future quitting or both. This study prospectively examined changes in cigarette consumption among adult smokers who relapsed from a quit attempt. It uses data from the first three waves of the International Tobacco Control Four-Country Survey (ITC-4), a random digit-dialed telephone survey of a cohort of over 9,000 adult smokers from the United Kingdom, United States, Canada, and Australia, followed up annually. Compared with those who did not make a quit attempt, relapsers were more likely to reduce consumption (average reduction of 0.7 vs. 3.4, respectively) over a mean period of 7 months between waves 1 and 2. Of the relapsers, 52% reduced their consumption by 5% or more, but 22% increased it. Smokers who smoked heavily at baseline, whose last quit attempt ended more recently, was of longer duration, and quit via a gradual cut-down method were all independently associated with reducing smoking following a failed attempt. These findings were similar across all four countries and were successfully replicated using waves 2–3 data. Change in consumption between waves 1 and 2 (whether increase or decrease) was maintained by a substantial number a year later (wave 3), but change did not undermine nor promote quitting between waves 2 and 3.